2011
DOI: 10.1186/1465-9921-12-25
|View full text |Cite
|
Sign up to set email alerts
|

Differences in allergen-induced T cell activation between allergic asthma and rhinitis: Role of CD28, ICOS and CTLA-4

Abstract: BackgroundTh2 cell activation and T regulatory cell (Treg) deficiency are key features of allergy. This applies for asthma and rhinitis. However with a same atopic background, some patients will develop rhinitis and asthma, whereas others will display rhinitis only. Co-receptors are pivotal in determining the type of T cell activation, but their role in allergic asthma and rhinitis has not been explored. Our objective was to assess whether allergen-induced T cell activation differs from allergic rhinitis to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…In this study of myeloid DCs from AR patients, we could link the aberrant pro-Th2 capacity (induction of IL-13 and IL-5) of DCs to ICOSL downregulation. Previous studies in mice [16,17] showed that ICOSL/ICOS interactions between DC and T cells lead to Th2 responses, and up-regulated ICOS in PBMC from AR patients underlined Th2 responses [18]. However, ICOS/ICOSL interaction also leads to Treg generation [17], as well as CD8a À DCs expressing higher ICOSL and IL-10 [27].…”
Section: Discussionmentioning
confidence: 98%
“…In this study of myeloid DCs from AR patients, we could link the aberrant pro-Th2 capacity (induction of IL-13 and IL-5) of DCs to ICOSL downregulation. Previous studies in mice [16,17] showed that ICOSL/ICOS interactions between DC and T cells lead to Th2 responses, and up-regulated ICOS in PBMC from AR patients underlined Th2 responses [18]. However, ICOS/ICOSL interaction also leads to Treg generation [17], as well as CD8a À DCs expressing higher ICOSL and IL-10 [27].…”
Section: Discussionmentioning
confidence: 98%
“…Increased IFN-γ release by both CD4+ and CD8+ T-cells from allergic adults was then found for responses to Der p 1 74 and then for children where there was a positive association with bronchial hyper-reactivity 75 , 76 . Botturi et al now report that peripheral blood mononuclear cells from asthmatics respond to purified lipopolysaccharide (LPS)-free Der p 1 by generating more IFN-γ producing T cells than cells from healthy subjects 77 and the recent comparison of tetramer staining of T-cells from HDM and birch-pollen allergic patients showed that in comparison to Bet v 1-binding cells, HDM-allergen-binding cells displayed a wide range of cytokines including IFN-γ 69 . There are reports indicating that T-cell from asthmatics with protracted HDM sensitization may have reduced IFN-γ 78 , 79 but there is growing realization of a contribution of Th1 responses to the pathogenesis of allergic disease 63 , 64 …”
Section: Immune Responses In Hdm Allergymentioning
confidence: 99%
“…Immunoregulatory IL-10 producing cells are increased after immunotherapy 52 and after repeated bee stings 80 but natural control of inhalant allergy by IL-10 is unclear, 81 , 82 especially for HDM where increased IL-10 production is found in responses of allergic subjects to allergens 75 , 77 , 83 and extracts, 82 , 84 , 85 including highly purified LPS-free Der p 1 77 . This might be the concomitant production of effector and regulatory responses since Heaton et al showed an inverse relationship between the size of skin test responses and IL-10 production 75 .…”
Section: Immune Responses In Hdm Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…This argues that both drugs and the doses tested are sufficient to efficiently attenuate the inflammatory response associated with the late asthmatic response, as has been previously documented [2,9,18]. The exact mechanism by which inhaled glucocorticoids have such pronounced effect on eosinophilic inflammation are not clear, although inhibitory effects on T-lymphocyte responses may be crucial [19]. …”
Section: Discussionmentioning
confidence: 95%